COVID-19 outbreaks in long-term care facilities—a nationwide population-based cohort study in Taiwan, May–July 2021 - Hao-Hsin Wu; Li-Jung Chien; Chiu-Hsia Su; Shu-Hui Tseng; Shan-Chwen Chang (Journal of the Formosan Medical Association, 2023)
Background/Purpose: Long-term care facilities (LTCFs) are high-risk settings for the novel coronavirus disease (COVID-19). The aim of the study was to describe the extent and the impacts of 2021 COVID-19 outbreaks on LTCFs in Taiwan. Methods: We retrospectively analyzed the data of each COVID-19 outbreak in LTCFs from May 15 to July 31, 2021 in Taiwan. We characterized the features of LTCFs with outbreaks and compared the characteristics of infected staff members and residents of the affected LTCFs. Results: COVID-19 outbreaks were reported in 16 LTCFs (0.9%). The outbreak was significantly associated with LTCFs with ≥50 beds [adjusted odds ratio (aOR), 6.3; 95%confidence interval [CI], 1.9–21.1] and location of Taipei metropolitan area (aOR, 4.6; 95%CI, 1.7–12.8). Resident cases accounted for 75.4% (203/269) of confirmed cases affected by outbreaks. The 30-day all-cause mortality was 24.2% for residents only and was significantly associated with age ≥65 years [adjusted hazard ratio (aHR, 4.3; 95%CI, 1.7–10.5)], presence of symptoms on diagnosis (aHR, 2.2; 95%CI, 1.3–3.7), and LTCF occupancy rate ≥80% (aHR, 3.0, 95%CI, 1.3–7.4). Conclusion: COVID-19 outbreaks have a critical impact on residents in LTCFs owing to the advanced age and high prevalence of chronic comorbidities in this population. Multi-pronged infection control measures and mass testing are vital for mitigating COVID-19 transmission in LTCFs.